Using Real-Time Ray Tracing in Game Action-Adventure ANGKARA "The Rise of Asura" - Aditama, Putu Wirayudi; Anggara, I Gede Adi Sudi; Alparizi, Jilmi (Sinkron : jurnal dan penelitian teknik informatika, 2024)
The pressing problems facing the games industry in Indonesia are first, the lack of developers who can meet the needs of the local market and the lack of adaptation of local content in games. Second, how to improve the optimization of the Ray Tracing process? To overcome these challenges, this research aims to design and build an action-adventure game model using Unreal Engine 5. By developing the Real-Time Ray Tracing (RTRT) feature. The game design will also utilize the latest technology such as Ray Tracing, and artificial intelligence to create an immersive and realistic gaming experience.  The method used in this research is GDLC (Game Development Life Cycle). The results of research using black box testing with components, character responsiveness, basic attacks, interaction with the environment, defense, enemy behavior, and optimization of Ray Tracing state that it has been validated.